ChemInform Abstract: Diastereoselective Nitrocyclopropanation of 2, 5‐Dihydrothiophene‐3‐carbaldehydes. Issue 18 (11th April 2013) - De Risi, Carmela; Benetti, Simonetta; Fogagnolo, Marco; Bertolasi, Valerio
Abstract An unprecedented domino Michael/α‐alkylation reaction between the aldehyde substrates and bromonitromethane allows the synthesis of thiabicyclohexane systems with good to excellent diastereoselectivities